2016
DOI: 10.12957/demetra.2016.19491
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade Nutricional E Físico-Química Em Cenoura (Daucus Carota L.) in Natura E Minimamente Processada

Abstract: Qualidade nutricional e físico-química em cenoura (Daucus carota l.) in natura e minimamente processada Nutritional and physicochemical quality in fresh and fresh cut carrot (Daucus carota l.) Resumo Introdução: A cenoura (Daucus carota L.) é uma das hortaliças mais produzidas e consumidas pela população brasileira e vem sendo comercializada tanto in natura quanto minimanente processada. Sua qualidade nutricional após o processamento mínimo pode sofrer alterações na composição centesimal e perfil físico-químic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
7
Order By: Relevance
“…The pH values found in this study are within those expected for carrots, since this culture is classified as a low acid food. Silva et al (2016) found a similar pH value (6.0) when studying carrots.…”
Section: Physical-chemical Characteristics and Carotenoid Contents Inmentioning
confidence: 55%
“…The pH values found in this study are within those expected for carrots, since this culture is classified as a low acid food. Silva et al (2016) found a similar pH value (6.0) when studying carrots.…”
Section: Physical-chemical Characteristics and Carotenoid Contents Inmentioning
confidence: 55%
“…Evaluating commercial carrot yield with different potassium doses, Silva et al (2016) conducted data adjustment with quadratic regression, in which the maximum point was 61.5 kg ha -1 of K 2 O, while fresh matter production reached a maximum of 87.7 kg ha -1 of K 2 O, which evidences that K influenced in the root's commercial classification.…”
Section: Resultsmentioning
confidence: 99%
“…Pensando nisso, optou-se em desenvolver um produto funcional fonte de pró vitamina A, e com o valor nutricional diferenciado. Para isso, foi produzida uma massa fresca com farinha de cenoura, sendo essa uma das hortaliças mais produzidas e consumidas pela população brasileira (SILVA et al, 2016).…”
Section: Massa Produzidaunclassified